Attentional Control and Suppressing Negative Thought Intrusions in Pathological Worry. (July 2015) - Fox, Elaine; Dutton, Kevin; Yates, Alan; Georgiou, George A.; Mouchlianitis, Elias
Adaptive behavior relies on the ability to effectively and efficiently ignore irrelevant information, an important component of attentional control. The current research found that fundamental difficulties in ignoring irrelevant material are related to dispositional differences in trait propensity to worry, suggesting a core deficit in attentional control in high worriers. The degree of deficit in attentional control correlated with the degree of difficulty in suppressing negative thought intrusions in a worry assessment task. A cognitive training procedure utilizing a flanker task was used in an attempt to improve attentional control. Although the cognitive training was largely ineffective, improvements in attentional control were associated with improvements in the ability to suppress worry-related thought intrusions. Across two studies, the findings indicate that the inability to control worry-related negative thought intrusions is associated with a general deficiency in attentional control.